Sesame Street. Love to learn [videorecording (DVD)]. (Warner Home Video, 2016)
Elmo and his friends love to learn about so many different things all the time. Elmo and Chris go on a camping trip and learn about what different animals eat. Also, Elmo and Leela teach Rosita about rainbows since she's never seen one. Join your Sesame Street friends as they learn about other fun and exciting things.